PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION DAN LECTURING UNTUK MENINGKATKAN PEMAHAMAN MAHASISWA TERHADAP MATERI ENGLISH TEACHING AND LEARNING THEORIES (ELT) - Rabbiyanti, Eva Nikmatul (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2016)
Merging two Methods between lecturing and Group Investigation are expected not only to develop active participation of students in the lecturing process but also to develop the ability of creative thinking, collaboration and presenting themselves in public, but the writer keep maintaining the use of lecturing methods to give control to the Â delivery of the key points of the materials. The research was conducted on students of D class of the 4th semester, TBI Programs of STAIN Pamekasan at 2013/2014 year, totaling 34 students. The method used was classroom action research by using two cycles, in each cycle consists of Planning, Implementation, and the reflection. The results of this study indicate that, the ability of students understanding of the course material ELT tends to increase in each cycle, with the average value of pre-cycle test was 45.29, and in the first cycle was 73.09, while in the second cycle was 79.00. with the percentage of completeness in cycle 1 was 85.29% while in the second cycle was 88.23%. Besides, the collaboration of this two models were also able to improve students analytical skills, the ability to express ideas and opinions in English, and also the ability to work together and present themselves in public. Based on the results of the study finally concluded, successful mechanism developed in this study consists of eleven stages, namely 1) the preparation phase, 2) the learning objective delivery, 3) aperseption delivery, 4) the new material delivery, 5) brain storming, 6) topics identification and grouping, 7) distribution of job decriptions, 8) conducting the investigation, 9) preparation of the final report, 10) Present the final report, 11) Evaluation of the achievement